2016
DOI: 10.1021/acssuschemeng.6b02043
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Enzymatic Synthesis of Biocompatible Polymers Made from Cholic Acid

Abstract: Polyesters are known biodegradable materials that are frequently used for biomedical applications that require biocompatibility. Their synthesis usually requires transition metal catalysts, which may become a source of contamination. In addition, using such compounds translates to extensive purification procedures, which do not agree with green chemistry principles. In addition to being renewable, enzymes such as lipases are milder for biological systems, and were studied for both ring-closure and ring-opening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
0
11
1
Order By: Relevance
“…Only a few cocrystallizing polymer systems have been reported during past several decades. In most cases, their synthesis is not easy and the T m difference is quite small. Gross’ group reported the copolymerization of ω-pentadecalactone (PDL) and ε-caprolactone (CL) catalyzed by Candida antartica lipase B (CALB), an enzyme with high efficiency for ring-opening polymerizations. P­(CL- co -PDL) random copolymers undergo isomorphous substitution and can cocrystallize over the entire composition range. , The possibility of cocrystallization provides an ideal situation for the design of 2W-SMPs. To the best of our knowledge, the strategy of using cocrystallizable monomers has not yet been used in the preparation of 2W-SMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few cocrystallizing polymer systems have been reported during past several decades. In most cases, their synthesis is not easy and the T m difference is quite small. Gross’ group reported the copolymerization of ω-pentadecalactone (PDL) and ε-caprolactone (CL) catalyzed by Candida antartica lipase B (CALB), an enzyme with high efficiency for ring-opening polymerizations. P­(CL- co -PDL) random copolymers undergo isomorphous substitution and can cocrystallize over the entire composition range. , The possibility of cocrystallization provides an ideal situation for the design of 2W-SMPs. To the best of our knowledge, the strategy of using cocrystallizable monomers has not yet been used in the preparation of 2W-SMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu and co-workers have synthesized CA-based cyclic polymers (Figure 4; P-6) using dilute Candida antarctica lipase B (CALB) enzyme solution via ring closing process. [62] They followed it with ring opening of the cyclic polymer using concentrated CALB which explores a nice prospect of enzyme assisted BAP design and synthesis. In addition, the same group worked on BA derived core confined polymer preparation to fabricate starlike supramolecular superstructures as reported by Myllymäki et al (Figure 4; P-7) [63] and Bertula et al [64] Recently, Cunningham et al have also designed CA cored PEG grafted star-shaped multi armed polymer [48] (Figure 5B) and folic acid (FA)-PEG armed CA-cored macromolecule for gene therapy applications.…”
Section: Design Trends Of Cholic Acid-based Polymersmentioning
confidence: 99%
“…The substrate concentration in as olvent is an important parameter for an enzymatic process because al ow substrate content may lead to the cyclization of oligomers to form macrocycles, [244,245] Reviews et al [249] determined that 350 wt %o fd iphenyl ether (vs. total mass of monomers) was optimal for the transesterification of bis(2,2,2-triflurorethyl) sebacate with 1,4-BDOa t3 7 8Cb yt he crude R. miehei lipase. Jiang et al showed that 150 wt %o fd iphenyle ther was the optimal solventa mount for the N435catalyzed transesterification reactiono fd iethyl succinate, dimethyl itaconate, and 1,4-BDO in diphenyl ether at 80 8C.…”
Section: Influence Of the Amountofsolventmentioning
confidence: 99%
“…The substrate concentration in as olvent is an important parameter for an enzymatic process because al ow substrate content may lead to the cyclization of oligomers to form macrocycles, [244,245] and the final molar mass can be decreased if the optimal conditions are not applied. As some examples,L inko ChemSusChem 2018, 11,3836 -3870 www.chemsuschem.org et al [249] determined that 350 wt %o fd iphenyl ether (vs. total mass of monomers) was optimal for the transesterification of bis(2,2,2-triflurorethyl) sebacate with 1,4-BDOa t3 7 8Cb yt he crude R. miehei lipase.…”
Section: Influence Of the Amountofsolventmentioning
confidence: 99%